Romance in the music of Obradors, Schubert, Gordon and Scarlatti - Gonzales, Kayla (Kansas State University, 2018)
This report is extended program notes that focus on romantic selections from four composers, prepared for a graduate vocal recital, completed in partial fulfillment of the requirement for the Master of Music degree. The recital was held April 25, 2017 at seven-thirty in the evening at Kirmser Hall on the campus of Kansas State University. The selections for this recital were chosen for their portrayal of the theme romance. The four composers selected for this report are Fernando Obradors, Franz Schubert, Ricky Ian Gordon and Alessandro Scarlatti. Each chapter will include biographical information on each composer, a textual analysis, as well as stylistic and technical considerations one must consider for the songs researched in this document. Romance is a topic that has often inspired composers and writers. This paper focuses on “romance” as a topic, which has been the focus of music for centuries. In vocal literature, a theme of romance can create an immediate connection to the listener as it is a topic that all genders can relate to.
Keywords: "Rompe Sprezza"; Ricky Ian Gordon; Al Amor; Alessandro Scarlatti; Franz Schubert; Fernando Obradors